If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(x + 5) = 4x + -8 Reorder the terms: 2 + -1(5 + x) = 4x + -8 2 + (5 * -1 + x * -1) = 4x + -8 2 + (-5 + -1x) = 4x + -8 Combine like terms: 2 + -5 = -3 -3 + -1x = 4x + -8 Reorder the terms: -3 + -1x = -8 + 4x Solving -3 + -1x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + -1x + -4x = -8 + 4x + -4x Combine like terms: -1x + -4x = -5x -3 + -5x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + -5x = -8 + 0 -3 + -5x = -8 Add '3' to each side of the equation. -3 + 3 + -5x = -8 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = -8 + 3 -5x = -8 + 3 Combine like terms: -8 + 3 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 | | (x^3+x^2+x+1)(5x-3)= | | 2(3+4)-6=48 | | 6x+4=24 | | 2(4x)=40 | | 9x-7+2x=8x+5-5x |